Influence of kind and level of fertilizers on some of growth and yield recipes of Eggplant in plastic houses under drip-irrigation system - Assi, Sabah Lateef (Journal of Kerbala for Agricultural Sciences, 2015)
Field experiment was conducted during 2012 2013growing season at al-musayab project to investigate the influence of kind and amount of fertilizers on growth and yield of eggplant in plastic houses under drip-irrigation system . under factorial experiment in RCBD with (3 ) replications , there were eight treatments resulted from four kinds of fertilizers (chemical fertilizer , poultry manure , sheep manure and cow manure) and two levels of organic fertilizers 25ton.h-1 and 50 Ton .h-1 , with two levels of chemical fertilizers, first was (100 kg N .h-1 , 5o kg P .h-1 and 40 kg K .h-1 ) and the second was (200 kg N .h-1 , 100 kg P. h-1 and 80 kg K . h-1) . The results showed that there was significant interaction effect between kind and fertilizer level on total yield , plant height , number of branches , leave and soil contents from N, P and K . The treatment of poultry manure at fertilizer's level of 50 ton .h-1 caused significant increase , It was given the higher yield 18.68 kg.m-2and a higher rang for all characteristics above as compared with all treatments .